Resilience of the Financial Performance of the Islamic Banking Industry in Indonesia to the Crisis - Esaputra, Ahmad Baihaqi; Majduddin, Rangga Dhia; Herlian, Erwin; Al-Afif, Rafiq Azzam; Indrasto, Haryo Bimo Budi; Nugroho, Jodi Setyo (Universitas Muhammadiyah Sorong, 2026)
This study examines the financial resilience of Islamic banking in Indonesia by comparing Bank Umum Syariah (BUS) and Unit Usaha Syariah (UUS) in responding to macroeconomic shocks during January 2015 until December 2023. A composite resilience index is constructed using a z-score approach that integrates profitability and leverage indicators. The Autoregressive Distributed Lag (ARDL) model is employed to capture short-run and long-run dynamics between resilience and its determinants, including total assets, third-party funds, inflation, the Bank Indonesia policy rate, and the COVID-19 shock. The results confirm long-run cointegration for both BUS and UUS, with notable differences in adjustment patterns. BUS demonstrates stronger structural resilience supported by asset scale, whereas UUS exhibits higher sensitivity to monetary tightening. Risk mapping further reveals latent vulnerabilities within the dual banking system. These findings highlight the need for differentiated supervision and a more selective approach in evaluating the readiness of UUS transformation into full-fledged Islamic banks.